2006
DOI: 10.1176/ps.2006.57.6.829
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Self-Report and Clinician Ratings on Two Inventories of Depressive Symptomatology

Abstract: Either the IDS-30 or the QIDS-16 self-report adequately assesses depressive symptom severity among public-sector outpatients with major depressive disorder. The briefer QIDS-16 may be preferred to save time and cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 39 publications
2
68
0
1
Order By: Relevance
“…The QIDS-SR was the most sensitive to treatment effects, which is consistent with extant literature and with the purpose of its original development (Rush et al 2006a;Rush et al 2006b;Rush et al 2003;2005;Trivedi et al 2004). Given that the DASS-21-DEP and the CES-D-10 have been less well studied in clinical samples, fewer psychometric evaluations have examined the treatment sensitivity of these measures.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The QIDS-SR was the most sensitive to treatment effects, which is consistent with extant literature and with the purpose of its original development (Rush et al 2006a;Rush et al 2006b;Rush et al 2003;2005;Trivedi et al 2004). Given that the DASS-21-DEP and the CES-D-10 have been less well studied in clinical samples, fewer psychometric evaluations have examined the treatment sensitivity of these measures.…”
Section: Discussionsupporting
confidence: 73%
“…The instrument was developed among clinical samples, and assesses the nine criterion symptom domains that define a major depressive episode according to the Diagnostic and Statistical Manual of Mental Disorders -Fourth Edition (DSM-IV-TR; American Psychiatric Association 2000). The QIDSSR is a shortened form of the 30-item Inventory of Depressive Symptomatology-Self report version (Rush et al 1996(Rush et al , 2000, and it has demonstrated equal or better sensitivity to symptom change compared to its longer counterpart (Rush et al 2003;2005, 2006bTrivedi et al 2004). The QIDS-SR has also performed well against a matched clinician-rated version (Rush et al 2006a, b;Trivedi et al 2004), and against 17-and 24-item versions of the clinician-rated Hamilton Rating Scale for Depression (Rush et al 2003;2005, a).…”
mentioning
confidence: 99%
“…Although the Spanish version of the QIDS-SR 16 is increasingly used (e.g., Bernstein et al, 2007;Feinberg et al, 2014;Lesser et al, 2008;Rush et al, 2006b;Trinh et al, 2011), to date, there is a striking lack of studies addressing its psychometric properties. By contrast, these have been recently examined for the parent IDS-SR 30 in a large Spanish sample of MDD patients (Gili et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The different scales show a considerable item overlap and include the DSM-IV [1] core symptoms of depression: all subscales (except ADAM2) include item 1 (depressed mood), 2 (guilt), 7 (work and interest) and 10 (anxiety psychic). None of these scales embodies all DSM-IV diagnostic depression criteria as the QIDS-C16 does Different studies in depressive patients have shown that the above-mentioned subscales are unidimensional and have comparable reliability and equal or even enhanced sensitivity to change compared to the HAMD17 (e.g., [6,11,13,18,20,45,51,52]). …”
Section: Introductionmentioning
confidence: 99%
“…The QIDS-C16-especially in comparative assessment with the HAMD17 and its subscales-is less researched. Trivedi and colleagues [61] as well as Rush and colleagues [51,52] demonstrated on depressed out-patient samples that the QIDS-C16 performed comparable to or even better than the IDS-C30 or the HAMD17 regarding sensitivity to symptom change and detection of response and depression remission.…”
Section: Introductionmentioning
confidence: 99%